Promosi Mesjid Raya Pulau Penyengat sebagai Daerah Tujuan Wisata di Tanjung Pinang Kepulauan Riau - trisoko, Riono gede (Komunitas Manajemen Kompetitif, 2015)
Abstract: Various attempts to make the Masjid Raya Island Biting as an object of religious tourism in the province of Riau Islands, has been carried out by the manager and local governments, among others, promotion to tourists both domestic and international travelers is done so that the level of tourist arrivals which may come as expected. The development of tourist traffic that comes to Masjid Raya Island Biting the average level of tourists who come to the Masjid Raya Island stinger where traffic levels continue to decline. Descriptive method used and the results of data analysis known that the Department of Culture and Tourism in increasing the number of visits such as: the availability of tourism information center, stinger island festival, held in cooperation with travel agencies and increased advertising on the island stinger. And the presence of Culture and Tourism today can say is good. With various promotions conducted by the relevant authorities so that the future can increase traffic. Keywords: Promotion, Tourism